Lighting and Color Preferences in Hajj Dormitory Bedrooms: Impact on Visitors’ Subjective Well-Being - Putri Ahmadina; Mahendra Wardhana (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DRPM), ITS, 2025)
The design of interior spaces significantly influences the subjective well-being of occupants, shaping their emotional states, comfort, and overall experience. Among the key environmental factors, lighting and interior color play a crucial role in creating a harmonious atmosphere, affecting mood, relaxation, and functional efficiency. However, Hajj dormitories, which serve as temporary accommodations for pilgrims and visitors, often suffer from suboptimal lighting and color schemes that may not fully support users’ well-being. This study investigates visitor preferences for lighting and color in Hajj dormitory bedrooms and their impact on subjective well-being. Through a systematic analysis and observations, it identifies how lighting conditions and color choices influence psychological responses, either enhancing tranquility or creating discomfort. Findings indicate that poor lighting configurations, such as dim illumination and lack of adjustability, contribute to decreased comfort and usability. Similarly, the selection of overly vibrant or dull color schemes negatively affects emotional balance, reducing the overall quality of the environment. To improve well-being in dormitory spaces, this study emphasizes the need for adaptive lighting solutions that cater to different user activities and color palettes that foster relaxation and positivity. By integrating the Positive Design Framework, dormitories can transition from purely functional accommodations to supportive environments that enhance both physical and psychological comfort. The study provides practical design recommendations that can be applied to Hajj dormitories and other communal accommodations, ensuring that interior spaces contribute to a more comfortable, emotionally supportive, and enriching experience for all users.